Kinetics and kinematics analysis of incremental cycling to exhaustion - Bini, R. R.; Diefenthaeler, F. (Sports Biomechanics, 2010)
Technique changes in cyclists are not well described during exhaustive exercise. Therefore the aim of the present study was to analyze pedaling technique during an incremental cycling test to exhaustion. Eleven cyclists performed an incremental cycling test to exhaustion. Pedal force and joint kinematics were acquired during the last three stages of the test (75%, 90% and 100% of the maximal power output). Inverse dynamics was conducted to calculate the net joint moments at the hip, knee and ankle joints. Knee joint had an increased contribution to the total net joint moments with the increase of workload (5-8% increase, p < 0.01). Total average absolute joint moment and knee joint moment increased during the test (25% and 39%, for p < 0.01, respectively). Increases in plantar flexor moment (32%, p < 0.01), knee (54%, p < 0.01) and hip flexor moments (42%, p = 0.02) were found. Higher dorsiflexion (2%, for p = 0.03) and increased range of motion (19%, for p = 0.02) were observed for the ankle joint. The hip joint had an increased flexion angle (2%, for p < 0.01) and a reduced range of motion (3%, for p = 0.04) with the increase of workload. Differences in joint kinetics and kinematics indicate that pedaling technique was affected by the combined fatigue and workload effects.